(untitled) (Zaporizhzhia Historical Review, 2021)
The article represents the first attempt to examine the process of formation of party and political forces in the South of Ukraine in March – August, 1917in the framework of the universal values and the perspective of creationof the Ukrainian State. The author aspires to illuminate all the spectrum of political forces which struggled in region for realization of the party programs.